A interlíngua de surdos falantes de Libras: uma análise de erros em produções textuais escritas em português como L2 - Batista, Eduardo Jorge Tabosa (2020)
Brazil currently has over a million and a half inhabitants with severe congenital hearing loss and, out of these, 46% reached only the second half of elementary school,wich is worrisome data considering the personal and social effect this reality may engender. Seeking to provide tools for the enhancement of Portuguese teaching to educational institutions for the deaf, the present study intended, based on Corder‟s error analysis methodology (1969), to analyze the interlingual, intralingual and ambiguous errors in the interlingual writing of deaf students to whom Portuguese is a second language. The students are congenitally deaf, have congenital hearing loss ranging from severe to profound, and are children of deaf parents or not. Besides, LIBRAS (acronym in Portuguese for Brazilian Sign Language) is their first language and Elementary, and they are Middle and High School students at the Instituto Cearense de Educação dos Surdos (Educational Institute of Ceará for the Deaf). With this intent, a survey, by way of a questionnaire, was conducted aiming to identify the participants‟ profile regarding general information about them and about the time and process of acquiring LIBRAS as well as the Portuguese language. A second instrument applied was a writing prompt in Portuguese, elaborated by the researcher, that was used to orient the participants‟ own individual text productions. The corpus is composed by the texts produced by means of this second instrument. This research sought to answer the following questions: How many and what types of errors – interlingual, intralingual or ambiguous –, do the participants make in their text productions in Brazilian Portuguese? How are the instruction levels characterized through the perspective of each one‟s predominant errors? Does the participants‟ interlanguage reach the highest school grade showing indications of fossilization? What are those indications? The theoretical and methodological framework used for the corpus analysis was respectively the interlanguage theory proposed by Corder (1969) and Selinker (1972) and the error analysis methodology proposed by Corder (1969). It was perceived that the Middle School 6th grade students presented merely a group of meaningless words. The High School 9th grade and 12th grade participants presented inter and intralingual errors in their productions, not presenting ambiguous errors. Moreover, the senior year students presented three times more intralingual errors than the ninth graders, and that all presented fossilization indicators.